Prolonged dialysis during ex vivo lung perfusion promotes inflammatory responses - De Wolf, Julien; Gouin, Carla; Jouneau, Luc; Glorion, Matthieu; Premachandra, Antoine; Pascale, Florentina; Huriet, Maxime; Estephan, Jérôme; Leplat, Jean-Jacques; Egidy, Giorgia; Richard, Christophe; Gelin, Valérie; et al. (Frontiers in Immunology, 2024)
Ex vivo lung perfusion (EVLP) has extended the number of transplantable lungs by reconditioning marginal organs. However EVLP is performed at 37°C without homeostatic regulation leading to metabolic wastes’ accumulation in the perfusate, and as a corrective measure, the costly perfusate is repeatedly replaced during the standard of care procedure. As an interesting alternative, a hemodialyzer could be placed on the EVLP circuit, that was previously shown to rebalance the perfusate composition, and to maintain lung function and viability without appearing to impact the global gene expression in the lung. Here, we assessed the biological effects of a hemodialyzer during EVLP by performing biochemical and refined functional genomic analyses over a 12 h procedure in a pig model. We found that dialysis stabilized electrolytic and metabolic parameters of the perfusate but enhanced the gene expression and protein accumulation of several inflammatory cytokines, and promoted a genomic profile predicting higher endothelial activation already at 6 h and higher immune cytokine signaling at 12 h. Therefore epuration of EVLP with a dialyzer, while correcting features of the perfusate composition and maintaining the respiratory function, promotes inflammatory responses in the tissue. This finding suggests that modifying the metabolite composition of the perfusate by dialysis during EVLP can have detrimental effects on the tissue response, and that this strategy should not be transferred as such to the clinic.